PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI BERBASIS APLIKASI CANVA PADA PEMBELAJARAN BANGUN DATAR KELAS IV SEKOLAH DASAR - Velisa, Velisa Andini Yusria; Yarisda, Yarisda Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the limited use of engaging, interactive, and easy-to-understand learning media, which are essential for fostering students' enthusiasm and motivation to learn. This condition highlights the need for developing learning media that are not only relevant to students' needs but also practical for teachers to implement. The purpose of this research is to evaluate the validity and practicality of Android-based learning media designed using Canva. This study adopts a Research and Development (R&D) approach using the ADDIE model, which consists of five systematic stages: Analyze, Design, Development, Implement, and Evaluate. The research subjects include three experts as validators, one fourth-grade teacher, and 20 fourth-grade students from SDN 45 Bungo Pasang. To collect data, this study employs several instruments, including expert validation sheets to assess the validity of the media and questionnaires to evaluate the practicality of the learning media based on the responses of teachers and students.